Effect and action mechanism of fibers on mechanical behavior of hybrid basalt-polypropylene fiber-reinforced concrete. (December 2021) - Fu, Qiang; Xu, Wenrui; Bu, MengXin; Guo, Bingbing; Niu, Ditao
Abstract: In this study, the mechanical properties of hybrid basalt fiber (BF) and polypropylene fiber (PF)-reinforced concretes (HBPRCs) having different matrix strengths were systematically studied, the action mechanism of the BFs and PFs was analyzed, and a prediction model of the mechanical properties of the HBPRCs was established. The results indicated that the BFs and PFs had a significant influence on the workability, compressive strength, flexural strength, and splitting tensile strengths of the concrete; however, they had little effect on elastic modulus. In general, the mechanical properties of the concrete were improved by adding only BFs and hybrid BFs and PFs when the fiber content was 0.1%. Although 0.2% hybrid BFs and PFs can reduce the compressive strength of the concrete, this composition can improve its flexural and splitting tensile strengths. With the increase in the matrix strength, the influence of the fibers on the mechanical properties of the concrete was weakened. BFs improved the strength of concrete more remarkably than PFs. Both BFs and PFs were beneficial for reducing the shrinkage cracking of the concrete. The synergistic effect of the BFs and PFs was advantageous for inhibiting the expansion of cracks in the concrete under loading and enhancing the integrity and mechanical properties of the concrete, particularly the flexural and splitting properties. Considering the factors of curing age, matrix strength, and BF and PF content, a prediction model of the mechanical properties of the HBPRCs was established, and its effectiveness was verified.